Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Moral Anak Di TK Aisyiyah Gonilan Kartasura Kabupaten Sukoharjo Tahun Ajaran 2015/2016 - Hari, Sandra Akhsepta; , Drs Ilham Sunaryo, M.Pd.AUD (2016)
Democratic parenting was parenting which parents give the freedom for children to do exploration in accordance with the capabilities with accompanying supervision of a parent. Children who have parents with democracy parenting will grow into a child who has a high self-confidence and be able to interact well with other people. The purpose of this research was to determine the relationship between democratic parenting parents and the moral development of children in kindergarten Aisyiyah Gonilan Kartasura in Sukoharjo Academic Year 2015/2016. This type of research was descriptive correlational research. The experiment was conducted in kindergarten Aisyiyah Gonilan Kartasura in Sukoharjo district. These samples included 59 children class for B, the sampling technique was a simple random sampling. The data were analyzed by using Product Moment Correlations. Based on the analysis result there was a relationship between a democratic parenting of parents to the moral development of children in kindergarten Aisyiyah Gonilan Kartasura In Sukoharjo Year 2015/2016. This was evidenced by the results of r Pearson correlation of 0.457 with a significance of 0.000 <0.05 (p = 0.000; p <0.05), which mean that Ho rejected, it mean that there was a relation between a democratic parenting of parents and morale children in kindergarten Aisyiyah Gonilan Kartasura in Sukoharjo Academic Year 2015/2016.